Optimum outcome achievement in partial nephrectomy for T1 renal masses: a contemporary analysis of open and robot‐assisted cases. (10th June 2017) - Maurice, Matthew J.; Ramirez, Daniel; Kara, Önder; Malkoç, Ercan; Nelson, Ryan J.; Fareed, Khaled; Stein, Robert J.; Fergany, Amr F.; Kaouk, Jihad H.
Abstract : Objectives: To compare optimum outcome achievement in open partial nephrectomy (OPN) with that in robot‐assisted partial nephrectomy (RAPN). Patients and methods: Using our institutional partial nephrectomy (PN) database, we reviewed 605 cases performed for unifocal clinical T1 renal masses in non‐solitary kidneys between 2011 and 2015. Tetrafecta, which was defined as negative surgical margins, freedom from peri‐operative complications, ≥80% renal function preservation, and no chronic kidney disease upstaging, was chosen as the composite optimum outcome. Factors associated with tetrafecta achievement were assessed using multivariable logistic regression, with adjustment for age, gender, race, Charlson comorbidity score, body mass index, chronic kidney disease, tumour size, tumour complexity and approach. Results: The overall tetrafecta achievement rate was 38%. Negative margins, freedom from complications, and optimum functional preservation were achieved in 97.1%, 73.6% and 54.2% of cases, respectively. For T1a masses, the tetrafecta achievement rate was similar between approaches ( P = 0.97), but for T1b masses, the robot‐assisted approach achieved significantly higher tetrafecta rates (43.0% vs 21.3%; P < 0.01). On multivariable analysis, the robot‐assisted approach had 2.6‐fold higher odds of tetrafecta achievement than the open approach, primarily because of lower peri‐operative morbidity, specifically related to wound complications. Positive surgical margin rates and renal function preservation were similar in the two approaches. Conclusions: Optimum outcomes are readily achieved regardless of PN approach. The robot‐assisted approach may facilitate optimum outcome achievement for 4–7‐cm masses by minimizing wound complications.